The Role Of Solidarity in A Multicultural Community Between Ethnic Chinese And Ethnic Minang In The Trade Process at Tanah Kongsi Padang Market Area - Primadani, Yossi; Utami, Sonia Pricillia; Enjelika, Fitri; Saputra, Hanafi (Journal of Humanity Studies, 2023)
The issue of natives and non-natives, minorities and the majority has become an exaggerated issue, giving rise to sentiment and disruption of relations between ethnic minorities and the ethnic majority. This article was deliberately written to see a portrait of harmony between Minang and Chinese ethnic groups in the city of Padang. This article aims to analyze the role of solidarity in a multicultural society which includes 2 ethnicities, namely the Minang and Chinese ethnicities in the Tanah Kongsi market area, Pondok, Padang, West Sumatra. In this research, the author uses qualitative methods by observing objects. Such as conducting observations, interviews with research informants and also using document studies. From this research the author sees a relationship of solidarity between traders in the market, Tanah Kongsi, Pondok, Padang. As can be seen when they interact, they still maintain friendly relations even though they are both competing in the trading process. And the way they help each other in the selling process, as well as by dividing the Los as a place to sell, where in the Tanah Kongsi market, not only provides halal sales, non-halal ones are also available in the market.